Islam dan Pancasila Perspektif Maqashid Syariah - Izuddinsyah Siregar (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Starting from the phenomenon in which certain groups, particularly among the younger generation, question the compatibility between Pancasila and Islam, this article employs a literature analysis approach to highlight how Prof. Yudian Wahyudi’s thought affirms that Pancasila aligns with Islamic values and can be understood as a manifestation of integrative tauhid. The concept of Maqashid Shariah, which emphasizes the objectives of Islamic law in realizing the welfare of humankind, is systematically connected to the principles of Pancasila encompassing divinity, humanity, unity, democracy, and social justice. The findings demonstrate that Pancasila can be understood as kalimatun sawa’, an inclusive language of national unity, as well as a tauhidic-maqashidic ideology capable of integrating religious and national values. These findings underscore the importance of strengthening dialogue, tolerance, and interfaith understanding in safeguarding Indonesia’s unity amidst contemporary socio-political challenges. Thus, this article contributes to the development of a national discourse that positions Pancasila and Islam as mutually supportive, while reinforcing the foundations of democracy, justice, and diversity in the nation's and state's life. Keywords: Islam, Pancasila, Maqashid Syariah